Aspek Hukum Pengaruh Transformasi Digital Terhadap Praktik Telemedicine Di Indonesia - Moh. Irsyad Hanif (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Health is a basic human need that continues to increase along with the progress of the times. Technological advances and lifestyle changes have led to a variety of new diseases, increasing the need for health services. Indonesia, with the fourth largest population in the world (272,229,372 people) and 10.14% of the population poor in 2021, faces significant health challenges. The COVID-19 pandemic has exacerbated the situation by limiting access to health services. Barriers to access, unequal distribution of services, and a shortage of doctors hinder efforts to realize the welfare of citizens as mandated by the 1945 Constitution. However, advances in information and communication technology have brought significant benefits in the health sector. Information technology has had a major impact on health and medicine, enabling the rapid, efficient, and accurate dissemination of information. One important development is the practice of telemedicine, which offers innovative solutions in health care.